Multiple schwannomas, including a plexiform variant, in a patient in the absence of neurofibromatosis I or II - Snehlata R Hingway (Journal of the Scientific Society, 2015)
Multiple schwannomatosis, is defined as two or more, pathologically proven schwannomas, without radiographic evidence of vestibular nerve tumor, below 18 years, or absence of VIII nerve dysfunction beyond 30 years with absence of stigmata of neurofibromatosis 2 (NF2). The plexiform schwannoma (PS) is a rare tumor. The gross appearance is an important diagnostic criterion for diagnosis of PSs. It is associated with NF2, which was ruled out in this case. Here we present a 50 year female patient with two nonintradermal schwannomas, in the supraclavicular and infraauricular deep soft tissues. One was plexiform, diagnosed on cytology and confirmed by histopathology. She also had multiple pulmonary and pleural lesions. Fine needle aspiration cytology smears from both supraclavicular and infraauricular lesions as well as the lung lesion sampled, showed spindle cells in a myxoid background, having wavy nuclei with pointed ends. Verocay body - like palisading of nuclei was noted.